Do Quantitative Measures of Research Productivity Correlate with Academic Rank in Oral and Maxillofacial Surgery?. Issue 8 (1st August 2015) - Susarla, Srinivas M.; Dodson, Thomas B.; Lopez, Joseph; Swanson, Edward W.; Calotta, Nicholas; Peacock, Zachary S.
Abstract : Academic promotion is linked to research productivity. The purpose of this study was to assess the correlation between quantitative measures of academic productivity and academic rank among academic oral and maxillofacial surgeons. This was a cross‐sectional study of full‐time academic oral and maxillofacial surgeons in the United States. The predictor variables were categorized as demographic (gender, medical degree, research doctorate, other advanced degree) and quantitative measures of academic productivity (total number of publications, total number of citations, maximum number of citations for a single article, I‐10 index [number of publications with ≥10 citations], and h‐index [number of publications h with ≥h citations each]). The outcome variable was current academic rank (instructor, assistant professor, associate professor, professor, or endowed professor). Descriptive, bivariate, and multiple regression statistics were computed to evaluate associations between the predictors and academic rank. Receiver‐operator characteristic curves were computed to identify thresholds for academic promotion. The sample consisted of 324 academic oral and maxillofacial surgeons, of whom 11.7% were female, 40% had medical degrees, and 8% had research doctorates. The h‐index was the most strongly correlated with academic rank (ρ=0.62, p<0.001). H‐indexes of ≥4, ≥8, and ≥13 were identified as thresholds for promotion to associate professor, professor, and endowed professor, respectively (p<0.001). This study found that the h‐index was strongly correlated with academic rank among oral and maxillofacial surgery faculty members and thus suggests that promotions committees should consider using the h‐index as an additional method to assess research activity.